Brevundimonas spp: Emerging global opportunistic pathogens. Issue 1 (1st January 2018) - Ryan, Michael P.; Pembroke, J. Tony
ABSTRACT: Non-fermenting Gram-negative bacteria are problematic in clinical locations, being one of the most prevalent causes of nosocomial infections. Many of these non-fermenting Gram-negative bacteria are opportunistic pathogens that affect patients that are suffering with underlying medical conditions and diseases. Brevundimonas spp., in particular Brevundimonas diminuta and Brevundimonas vesicularis, are a genus of non-fermenting Gram-negative bacteria considered of minor clinical importance. Forty-nine separate instances of infection relating to Brevundimonas spp were found in the scientific literature along with two pseudo-infections. The majority of these instances were infection with Brevundimonas vesicularis (thirty-five cases – 71%). The major condition associated with Brevundimonas spp infection was bacteraemia with seventeen individual cases/outbreaks (35%). This review identified forty-nine examples of Brevundimonas spp. infections have been discussed in the literature. These findings indicate that infection review programs should consider investigation of possible Brevundimonas spp outbreaks if these bacteria are clinically isolated in more than one patient.